Beginning Oracle SQL - Haan, Lex de (Apress, 2012)
This book was born from a translation of a book originally written by Lex de Haan in Dutch. That book was first published in 1993, and went through several revisions in its native Dutch before Lex decided to produce an English version. Apress published that English version in 2005 under the title “Mastering Oracle SQL and SQL*Plus”. The book has since earned respect as excellent, accurate, and concise tutorial on Oracle’s implementation of SQL. While SQL is a fairly stable language, there have been changes to Oracle’s implementation of it over the years. The book you are holding now is a revision of Lex’s original, English-language work. The book has been revised to cover new developments in Oracle SQL since 2005, especially those in Oracle Database 11g Release 1 and Release 2. The book has also been given the title “Beginning Oracle SQL”. The new title better positions the book in Apress’s line, better refects the content, fits better with branding and marketing efforts, and marks the book as a foundational title that Apress intends to continue revising and publishing in the long term.